Prior immunological memory to pertussis toxin affects the avidity development of anti-PT IgG antibodies after acellular pertussis booster vaccination - Knuutila, Aapo; Ahvenainen, Niina; Barkoff, Alex-Mikael; Mertsola, Jussi; van Gageldonk, Pieter; Buisman, Annemarie; Valente Pinto, Marta; Kelly, Dominic; He, Qiushui (Taylor & Francis, 2026)
Acellular pertussis vaccines are used in many countries. Since the quantity of antibodies after vaccination wanes quickly, to study functional antibody properties is important for evaluating long-lasting protection. Additionally, substantial variation in the quantity and quality of antibodies exists after vaccination in different age groups. The avidity of antibodies to pertussis toxin (PT) after Tdap3-IPV booster vaccination was studied in children, adolescents, young adults, and older adults. Serum samples (N = 365) were collected before, one month, and one year after vaccination in Finland, the Netherlands, and the United Kingdom. The samples were diluted to equal anti-PT IgG concentrations, and avidity was measured utilizing urea as a chaotropic agent. Although concentrations of anti-PT IgG at baseline were similar between the countries, avidity was higher in the Netherlands and United Kingdom. Despite increased anti-PT IgG concentrations in participants after vaccination, an increase in avidity was noted mainly among participants with low pre-vaccine avidity. Avidity was significantly lower in older adults in comparison to children (p < 0.01) and adolescents (p = 0.03) in Finnish participants one month after vaccination. Avidity after booster was influenced by the initial level of avidity, which could be linked to vaccination background, age, and prior disease exposure. The development of avidity from one month after vaccination to a year after was highly individual, with some participants having either a decrease, an increase or a stagnant level of avidity. This emphasizes that long-term follow-up of avidity is essential. Booster vaccination seems particularly beneficial to individuals with low antibody avidity before vaccination.